Assessment of transportation expenditure in affordability measurement of rental low-cost housing schemes in Kuala Lumpur Federal Territory, Malaysia. / Zaharah Mohd Yusoff - Mohd Yusoff, Zaharah (Institute of Graduate Studies, UiTM, 2012)
Low-cost housing development schemes have given good opportunities for poor families to own or rent a house. Many programmes were undertaken by the government of Malaysia to house lower-income families since the colonial period before Malaysia’s Independence in 1957. The emphasis on providing low-cost housing was put as a main agenda item in the First to Ninth Malaysia Plans (1966-2010). It was developed by joint-venture programmes between public and private agencies through policy enforcement. Lately, there are a growing number of researchers worldwide discussing another issue of living; that is the increase of transportation costs. This new phenomenon has caused people to re-evaluate what true affordability means. The earlier income-based method for identifying lower-income families is no longer practical in the current economic situation and an improved method is needed.